2007
DOI: 10.1152/ajplung.00412.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin ameliorates lipopolysaccharide-induced acute lung injury in rats

Abstract: Adrenomedullin (AM), an endogenous peptide, has been shown to have a variety of protective effects on the cardiovascular system. However, the effect of AM on acute lung injury remains unknown. Accordingly, we investigated whether AM infusion ameliorates lipopolysaccharide (LPS)-induced acute lung injury in rats. Rats were randomized to receive continuous intravenous infusion of AM (0.1 microg x kg(-1) x min(-1)) or vehicle through a microosmotic pump. The animals were intratracheally injected with either LPS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 55 publications
2
58
1
Order By: Relevance
“…In particular, adrenomedullin may decrease infection-induced organ damage, 5 inflammation, and apoptosis. 3 Our observational design cannot unravel this protective role, yet we confirm previous observations that high MR-proADM levels add a prognostic marker in patients clinically deemed to be high risk for death.…”
Section: Psi Class IIIsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, adrenomedullin may decrease infection-induced organ damage, 5 inflammation, and apoptosis. 3 Our observational design cannot unravel this protective role, yet we confirm previous observations that high MR-proADM levels add a prognostic marker in patients clinically deemed to be high risk for death.…”
Section: Psi Class IIIsupporting
confidence: 83%
“…1 Adrenomedullin is a peptide produced by multiple tissue types during physiologic stress, and has pluripotent function, including vasodilatory, antimicrobial, and antiinflammatory activity. 2 In animal models of sepsis, [3][4][5] exogenous adrenomedullin reduces acute lung injury, vascular permeability, and death; endogenous overexpression similarly ameliorates the septic insult. Human data are sparse, but early studies 6,7 reported high adrenomedullin levels associated with increased vasodilation and severity of illness in systemic inflammation and septic shock.…”
mentioning
confidence: 99%
“…Conceptually, this seeming dichotomy probably represents a ''fire versus firefighter'' epiphenomenon, where the proportional presence of firefighters at a fire reflects their protective, rather than causative, role [40]. Therefore, elevated pro-adrenomedullin levels seen with increased illness severity and mortality might represent an endogenous, protective role for adrenomedullin [40], in an attempt to decrease inflammation, apoptosis and infection-induced organ damage [41,42]. Henceforth, higher proadrenomedullin levels would reflect greater inflammatory stimuli or more pronounced systemic repercussions of the disease, possibly explaining this biomarker's predictive properties in COPD and other respiratory conditions, such as pneumonia, sepsis and dyspnoea with and without heart failure [40,[43][44][45][46][47][48].…”
Section: Pro-adrenomedullin As An Alternative To the 6mwt For Mortalimentioning
confidence: 99%
“…Other studies have further demonstrated that adrenomedulin, a peptide structurally related to CGRP, can act via both CGRP and adrenomedulin receptors to mediate its effects. Adrenomedulin has also been implicated in ROS generation (Yoshimoto et al 1998;Dakhama et al 2004;Rahman et al 2006;Itoh et al 2007;Kim et al 2010). Furthermore, CGRP has been found to play an important role in protecting myocytes, kidney cells, pancreatic B cells, and liver cells from the potentially damaging effects of ROS (She et al 2003;Kroeger et al 2009;Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%